2020
DOI: 10.1186/s40643-020-00334-6
|View full text |Cite|
|
Sign up to set email alerts
|

A novel strategy for efficient disaccharides synthesis from glucose by β-glucosidase

Abstract: Oligosaccharides have important therapeutic applications. A useful route for oligosaccharides synthesis is reverse hydrolysis by β-glucosidase. However, the low conversion efficiency of disaccharides from monosaccharides limits its large-scale production because the equilibrium is biased in the direction of hydrolysis. Based on the analysis of the docking results, we hypothesized that the hydropathy index of key amino acid residues in the catalytic site is closely related with disaccharide synthesis and more h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Rational design (Hydropathy index for enzyme activity) Site-directed mutation ---Transglycosylation: ↑disaccharides productivity by 3.5-fold. [28] Bacillus sp. D1 (BglD1) Semi-rational design Site-directed mutagenesis ---Transglycosylation: ↑ GOS productivity by 11.5%.…”
Section: Trichoderma Reeseimentioning
confidence: 99%
See 1 more Smart Citation
“…Rational design (Hydropathy index for enzyme activity) Site-directed mutation ---Transglycosylation: ↑disaccharides productivity by 3.5-fold. [28] Bacillus sp. D1 (BglD1) Semi-rational design Site-directed mutagenesis ---Transglycosylation: ↑ GOS productivity by 11.5%.…”
Section: Trichoderma Reeseimentioning
confidence: 99%
“…As shown in Table 4, the rational design of targeted BGL catalytic tunneling of subsite residues provides methodological strategies: (1) reducing the binding in glycone (−) subsites; (2) increasing the affinity in aglycone (+) subsites; and (3) disrupting the binding of catalytic water: mainly by removing the hydrogen-bonding interactions with the catalytic water and the retention of nucleophilic water molecules at key amino acid residues, or enhancing the hydrophobicity at the active site entry or acceptor subsite [95]. For example, the Hydropathy Index For Enzyme Activity (HIFEA) strategy to reduce the hydrophilic index of BGL amino acid residues has been used for the rational design of oligosaccharide synthesis [28]. ↑ Disaccharides productivity by 3.5-fold.…”
Section: Improving Transglycosylationmentioning
confidence: 99%
“…In the original publication of the article (Niu et al 2020 ), the statement in the Funding information section was incorrectly given as ‘the National Key R&D Program of China (No. 2018YFA090010)’ and should have read ‘the National Key R&D Program of China (No.…”
Section: Correction To: Bioresour Bioprocess (2020) 7:45 Ht...mentioning
confidence: 99%
“…The biosynthesis of laminaribiose from glucose by β-glucosidase or from glucose and glucose 1-phosphate (G1P) by laminaribiose phosphorylase (LBP, EC 2.4.1.30) has recently received increasing attention due to the readily accessible substrate, mild reaction conditions, environment-friendly process, and excellent regio- and stereoselectivity . The synthesis of laminaribiose by glycosidases has several benefits that embody simplicity, accessibility, and easy operations, although the broad substrate specificity of β-glucosidase synthesizes three main products (laminaribiose, sophorose, and cellobiose). , In contrast, LBP, which catalyzes ATP-independent phosphorolysis reactions with strict regioselectivity, is the ideal enzyme for the transformation of readily accessible saccharides to laminaribiose. Many studies have investigated the use of sucrose or maltodextrin as a provider of G1P catalyzed by sucrose phosphorylase (SP) or α-glucan phosphorylase (αGP) . Muller et al reported the production of laminaribiose from sucrose and glucose catalyzed by SP and LBP, in which the reaction was carried out at 35 °C with a final yield of 55%.…”
Section: Introductionmentioning
confidence: 99%
“…13 The synthesis of laminaribiose by glycosidases has several benefits that embody simplicity, accessibility, and easy operations, although the broad substrate specificity of β- glucosidase synthesizes three main products (laminaribiose, sophorose, and cellobiose). 14,15 In contrast, LBP, which catalyzes ATP-independent phosphorolysis reactions with strict regioselectivity, is the ideal enzyme for the transformation of readily accessible saccharides to laminaribiose. 16−18 Many studies have investigated the use of sucrose or maltodextrin as a provider of G1P catalyzed by sucrose phosphorylase (SP) or α-glucan phosphorylase (αGP).…”
Section: ■ Introductionmentioning
confidence: 99%